2014
DOI: 10.1371/journal.pone.0105555
|View full text |Cite|
|
Sign up to set email alerts
|

Intermittent Hypoxia Effect on Osteoclastogenesis Stimulated by Neuroblastoma Cells

Abstract: BackgroundNeuroblastoma is the most common extracranial pediatric solid tumor. Intermittent hypoxia, which is characterized by cyclic periods of hypoxia and reoxygenation, has been shown to positively modulate tumor development and thereby induce tumor growth, angiogenic processes, and metastasis. Bone is one of the target organs of metastasis in advanced neuroblastoma Neuroblastoma cells produce osteoclast-activating factors that increase bone resorption by the osteoclasts. The present study focuses on how in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…CM: conditioned media; mRNA: messenger RNA; RANKL: nuclear factor-κB ligand; siNC: HIF-1α silencer negative control; siRNA: small interfering RNA; TRAP: tartrate-resistant acid phosphatase [Color figure can be viewed at wileyonlinelibrary.com] (Johnson, Schipani, & Giaccia, 2015). It is been proven that HIF-1α also increases on exposure to osteoclastogenic cytokines during monocytes differentiating into osteoclasts (Bhaskara, Mohanam, Gujrati, & Mohanam, 2014;Utting, Flanagan, Brandaoburch, Orriss, & Arnett, 2010). Some evidence suggests that HIF-1α is also required for osteoclasts activation and bone loss in osteoporosis (Miyauchi et al, 2013;Tando et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…CM: conditioned media; mRNA: messenger RNA; RANKL: nuclear factor-κB ligand; siNC: HIF-1α silencer negative control; siRNA: small interfering RNA; TRAP: tartrate-resistant acid phosphatase [Color figure can be viewed at wileyonlinelibrary.com] (Johnson, Schipani, & Giaccia, 2015). It is been proven that HIF-1α also increases on exposure to osteoclastogenic cytokines during monocytes differentiating into osteoclasts (Bhaskara, Mohanam, Gujrati, & Mohanam, 2014;Utting, Flanagan, Brandaoburch, Orriss, & Arnett, 2010). Some evidence suggests that HIF-1α is also required for osteoclasts activation and bone loss in osteoporosis (Miyauchi et al, 2013;Tando et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, in the in vivo situation, monocytes and osteoclasts do not exist in isolation but are surrounded by osteoblasts, fibroblasts, and other cellular components of the bone microenvironment that will also be exposed to local hypoxia. Co-culture of monocytes with stromal cells including osteoblasts, fibroblasts, and cancer cells has revealed that hypoxia stimulates local production of pro-osteoclastogenic cytokines including RANKL, 24 , 25 vascular endothelial growth factor (VEGF), 24 27 M-CSF, 27 insulin-like growth factor 2, 28 and growth differentiation factor 15, 29 as well as inhibiting production of osteoprotegerin (OPG), a soluble decoy receptor for RANKL that inhibits osteoclast formation and activity. 30 …”
Section: Hypoxia Stimulates Osteoblast-mediated Osteoclastogenesismentioning
confidence: 99%
“…Serum tartrate-resistant acid phosphatase (TRAP) is widely accepted in clinical practice and scientific research as a highly specific and sensitive index of bone metabolism reflecting changes in bone resorption [ 17 ]. Research data have indicated that the CIH of OSAS may affect the kidney, gastrointestinal tract, osteoblasts, osteoclasts, sympathetic nerves, leptin, and an inflammatory response resulting in abnormal bone metabolism [ 18 , 19 ]. However, changes in the biochemical indexes of bone metabolism in an environment of CIH are not fully understood.…”
Section: Introductionmentioning
confidence: 99%